Abdominal parietal necrotizing cellulitis: Due to spontaneous retro-peripheral perforation of a descending colon cancer - Croci, Fabio; Gastambide, Carmelo; Pérez Penco, Ernesto (Cirugía del Uruguay, 1986)
Description of a case of spontaneous necrotizing cellulitis of the anterolateral abdominal wall caused by a retroperitoneal perforation of a descending colon carcinoma. The anatomopathological examination showed the coexistence of a specifically tuberculous colitis. Clinical, diagnostic and therapeutic considerations are made on this unfrequent complication of colopathies.